Isla Gorgona, strategic enclave for conservation efforts in the Eastern Tropical Pacific - Giraldo, Alan (2014)
Gorgona, located in the southern zone of the Pacific Ocean of Colombia, is an insular territory at 35km in a straight line from the continental margin. Although historically this island was used in different forms, since 1984 it has been among the most important protected marine areas of the Colombian Pacific Ocean. Here we review the historical development of scientific research in Gorgona island and its importance for marine and coastal conservation in the Colombian Pacific region. The island is an strategic location for the Eastern Tropical Pacific Conservation Corridor. Its ecological status is acceptable but the populations of Bradypus variegatus and Proechymis simispinosus are too small and monitoring and scientific programs need to continue. Rev. Biol. Trop. 62 (Suppl. 1): 1-12. Epub 2014 February 01.